2019
DOI: 10.1002/ejp.1479
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition, perseverative thinking, and pain catastrophizing: A moderated‐mediation analysis

Abstract: Background Pain catastrophizing is linked to a range of negative health and treatment outcomes, although debate continues about how best to define and treat it, since most interventions produce only modest benefit. This study aimed to contribute to theory‐driven development of these treatments by exploring the role of perseverative thinking in pain catastrophizing, along with the higher order beliefs, called metacognitions that might shape it. Methods An Internet sample of 510 people with chronic pain (≥3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
(75 reference statements)
1
24
0
Order By: Relevance
“…Recent studies support the importance of the metacognitive aspect of rumination when characterizing pain catastrophizing (Schütze, 2016;Schütze et al, 2020). Many pain patients with high levels of catastrophizing believe that rumination help to solve problems and to prepare handling future threats, even when the sense of uncontrollability over ruminative thoughts produces negative consequences on mental health (Schütze et al, 2017).…”
Section: Empirical Support In Pain Researchmentioning
confidence: 99%
“…Recent studies support the importance of the metacognitive aspect of rumination when characterizing pain catastrophizing (Schütze, 2016;Schütze et al, 2020). Many pain patients with high levels of catastrophizing believe that rumination help to solve problems and to prepare handling future threats, even when the sense of uncontrollability over ruminative thoughts produces negative consequences on mental health (Schütze et al, 2017).…”
Section: Empirical Support In Pain Researchmentioning
confidence: 99%
“…One of the psychological alterations that has been associated with FM is pain catastrophizing, a specific psychosocial construct of pain, which includes cognitive and emotional processing, sense of helplessness, pessimism, and rumination about pain-related symptoms [2]. Pain catastrophizing has been associated with pain severity and disability [3], which is being considered a risk factor for pain chronification [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results have not found a direct effect of positive Metacognitions on functionality, coping or pain intensity, it cannot be said that these types of cognitions do not have final effects on the pain experience process, since, as can be seen in the model, this variable does generate an impact on the variables: Negative metacognitions and Self-efficacy to pain, that is, it can be stated that in this study its effect may be indirect on them. In contrast to this directionality of the effect, in their recent publication, Schütze et al (2020) has suggested that pain intensity may have an influence on positive Metacognitions, although this directionality of effect was not considered in this study.…”
Section: Self-regulation Of Pain In Fibromyalgiamentioning
confidence: 72%